2019
DOI: 10.1080/02673843.2019.1596823
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stress on students in secondary school and higher education

Abstract: Students in secondary and tertiary education settings face a wide range of ongoing stressors related to academic demands. Previous research indicates that academic-related stress can reduce academic achievement, decrease motivation and increase the risk of school dropout. The longer-term impacts, which include reduced likelihood of sustainable employment, cost Governments billions of dollars each year. This narrative review presents the most recent research concerning the impact of academic-related stress, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
448
0
52

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 696 publications
(521 citation statements)
references
References 53 publications
21
448
0
52
Order By: Relevance
“…Findings on association between third year of study and drug use are comparable to an eight year longitudinal analysis in Mid-Atlantic that reported highest annual peak of marijuana use in year three of study (8). This could be attributed to factors like academic-related stress (24), poor social skills thus increased vulnerability to peer pressure to use drugs (25), limited physical activities (26) and poor quality dating relationships (27). All the aforementioned factors combined increased vulnerability to stress and depression which in turn heightens drug use as a form of self medication.…”
Section: Discussionsupporting
confidence: 65%
“…Findings on association between third year of study and drug use are comparable to an eight year longitudinal analysis in Mid-Atlantic that reported highest annual peak of marijuana use in year three of study (8). This could be attributed to factors like academic-related stress (24), poor social skills thus increased vulnerability to peer pressure to use drugs (25), limited physical activities (26) and poor quality dating relationships (27). All the aforementioned factors combined increased vulnerability to stress and depression which in turn heightens drug use as a form of self medication.…”
Section: Discussionsupporting
confidence: 65%
“…The current study was conducted on medical students. Students suffer a stressful study process during their undergraduate course which causes high levels of stress to be reported in students [ 17 ]. Other sources of stress could derive from time or economic problems [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, they feel useless and inadequate as a student, losing satisfaction and personal accomplishment [2,9] ( [10] for a review). Several studies have shown the detrimental effects of burnout in adolescents in terms of dropout, poor performance, and other clinical or subclinical conditions later on [11][12][13][14][15]. According to Alarcon and colleagues [3], who applied the conservation of resources theory [16] to educational tracks, school burnout can be considered as the product of the consumption of available resources.…”
Section: School Burnout and Students Resourcesmentioning
confidence: 99%